Bombus impatiens (Hymenoptera: Apidae) display reduced pollen foraging behavior when marked with bee tags vs. paint - Switzer, Callin Morgan; Combes, Stacey A. (Journal of Melittology, 2016)
Numbered bee tags, developed for marking honey bees (Apis mellifera Linnaeus), are glued to the mesosoma of many bees to uniquely identify them.  We recorded whether or not bees sonicated to collect pollen after being marked, and we compared the sonication frequency, sonication length, and wing beat frequency of Bombus (Pyrobombus) impatiens Cresson that were tagged with bee tags vs. marked with paint.  We found that bees with tags glued to their mesosoma had no significant change in wing beat frequency, sonication frequency, or sonication length, relative to bees that were marked with paint; however, we found that the probability of collecting pollen via sonication after being marked was much lower for bees marked with bee tags vs. paint.